ANALISIS PENGELOLAAN SAMPAH DI PASAR TRADISIONAL: STUDI KASUS PASAR-PASAR KAPANEWON PIYUNGAN BANTUL - Maulinda Rahmawati; Lucky Herawati; Rois, Ibnu (Poltekkes Kemenkes Bengkulu, 2024)
Waste management in traditional markets, such as those in Kapanewon Piyungan, presents unique challenges compared to household waste management, primarily due to the predominance of organic waste from food scraps and agricultural products. This study aims to evaluate and analyze the waste management systems in three major markets in Kapanewon Piyungan: Pasar Piyungan, Pasar Panasan, and Pasar Kembangsari. A descriptive qualitative and quantitative approach was used, collecting data through measurement of waste volume and composition using digital scales, and observation of waste sorting systems, waste receptacles, transportation facilities, temporary waste storage (TPS), the use of personal protective equipment (PPE) by sanitation workers, and waste processing methods. Findings indicate that Pasar Piyungan has a more advanced waste management system, including composting of organic waste, while Pasar Panasan and Pasar Kembangsari do not process waste and instead transport it directly to the landfill. Although all three markets provide waste bins and transportation facilities, there are deficiencies in meeting technical standards, such as improper placement of TPS and inadequate facilities. Additionally, the use of PPE by sanitation workers varies among markets, with Pasar Piyungan and Pasar Panasan showing better compliance compared to Pasar Kembangsari. In conclusion, despite efforts to improve waste management, there is a need for technical enhancements and increased awareness to ensure more effective and sustainable waste management across all markets in Kapanewon Piyungan.